2018
DOI: 10.1111/micc.12443
|View full text |Cite
|
Sign up to set email alerts
|

Substance P ameliorates tumor necrosis factor‐alpha‐induced endothelial cell dysfunction by regulating eNOS expression in vitro

Abstract: SP can protect the vascular endothelium against inflammation-induced damage through modulation of the Akt/eNOS/NO signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…After 24 h, SP was added to the damaged ADSCs at a concentration of 100 nM ( Figure 2 A). This dose of SP was determined based on previous reports [ 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 24 h, SP was added to the damaged ADSCs at a concentration of 100 nM ( Figure 2 A). This dose of SP was determined based on previous reports [ 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Substance-P (SP) is an endogenous neuropeptide that interacts with neurokinin receptor 1 (NK-1R). SP has been reported to stimulate cell proliferation and prevent apoptosis under inflammatory or oxidative stress by activating the extracellular signal-regulated kinases 1/2 (ERK 1/2) or Akt and by translocating β-catenin to cell nuclei [ 15 , 16 , 17 , 18 ]. SP could suppress inflammation to promote tissue repair in severe diseases by modulating the immune cell profile in circulation-associated and lymphoid organs [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…SP is known to suppress highly activated immune response [ 35 37 , 43 ], protect the vascular endothelium [ 42 ], and restore stem cell functions [ 40 , 41 ] under disease conditions. These functions were proven in different non-clinical disease models.…”
Section: Discussionmentioning
confidence: 99%
“…SP, a new BMSC mobilizer [ 38 ], can not only restore the BMSC pool by repopulating BMSCs [ 39 ] but also block their senescence by potentiating their ability to secrete anti-inflammatory cytokines [ 40 , 41 ]. Moreover, SP protects the vascular endothelium and promotes angiogenesis to inhibit the progression of vascular diseases [ 42 – 44 ]. Interestingly, the expression of SP in BM is severely decreased and that of its receptor NK-1R is enhanced in osteoporosis [ 45 , 46 ], indicative of its relevance to bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al demonstrated that SP acts not only as a messenger that indicates injury but also as a mobilizer of CD29 + stromal-like cells, which are produced in the bone marrow and participate in wound healing (14). Recent studies have shown that SP has an anti-inflammatory effect by inhibiting tumor necrosis factor-alpha (TNF-α) and inducing IL-10 (15)(16)(17). In the case of ischemia reperfusion injury (IRI), SP improves the injury by increasing MSC and endothelial progenitor cell (EPC) in the blood circulation and reducing TNFα (18).…”
Section: Introductionmentioning
confidence: 99%